2022
DOI: 10.3389/fnsyn.2022.861215
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Dependent Synaptic Plasticity at the Hippocampal Mossy Fiber Terminal

Abstract: Cyclic adenosine monophosphate (cAMP) is a crucial second messenger involved in both pre- and postsynaptic plasticity in many neuronal types across species. In the hippocampal mossy fiber (MF) synapse, cAMP mediates presynaptic long-term potentiation and depression. The main cAMP-dependent signaling pathway linked to MF synaptic plasticity acts via the activation of the protein kinase A (PKA) molecular cascade. Accordingly, various downstream putative synaptic PKA target proteins have been linked to cAMP-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 186 publications
0
15
0
Order By: Relevance
“…It is important to consider that over timescales longer than those addressed in this study, G i/o -dependent actuators are anticipated to exert additional influence on canonical cAMP-protein kinase A pathways. These pathways have previously been implicated in, for instance, the synaptic incorporation of AMPA receptors (Esteban et al, 2003), postsynaptic long-term potentiation (Yasuda et al, 2003), presynaptic long-term plasticity (Sakaba and Neher, 2003; Atwood et al, 2014; Shahoha et al, 2022), synapse formation (Liang et al, 2021) as well as neuronal migration and neurite growth (Bony et al, 2013). Taken together, we demonstrate that hM4Di can serve as a valuable presynaptic silencer in mice shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that over timescales longer than those addressed in this study, G i/o -dependent actuators are anticipated to exert additional influence on canonical cAMP-protein kinase A pathways. These pathways have previously been implicated in, for instance, the synaptic incorporation of AMPA receptors (Esteban et al, 2003), postsynaptic long-term potentiation (Yasuda et al, 2003), presynaptic long-term plasticity (Sakaba and Neher, 2003; Atwood et al, 2014; Shahoha et al, 2022), synapse formation (Liang et al, 2021) as well as neuronal migration and neurite growth (Bony et al, 2013). Taken together, we demonstrate that hM4Di can serve as a valuable presynaptic silencer in mice shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, low-frequency stimulation of mossy fibers induces presynaptic LTD by inactivating AC via metabotropic glutamate receptors (Tzounopoulos et al ., 1998). PKA is considered by far the most major molecule that mediates LTP/LTD at the mossy fiber terminals, and the target molecules include many active zone and vesicular proteins such as Rab3a, synapsin, RIM1a, synaptotagmin, and tomosyn (Shahoha et al ., 2022). Some of these proteins are also implicated in memory defect in Drosophila (Knapek et al ., 2010; Chen et al ., 2011; Niewalda et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KD of C1ql2 in WT DGN recapitulated the Bcl11b phenotype with impaired SV recruitment and loss of LTP, supporting the specificity of C1ql2 function. MF-LTP, which manifests as a long-term increase in presynaptic vesicle release probability (P r ) (Shahoha et al, 2022), directly depends on the distribution of SV in the proximity of the AZ. Recent studies have shown that the increase in P r involves the recruitment of new AZ and an increase in the number of docked and tethered vesicles, corresponding to the readily releasable pool of SV (Orlando et al, 2021; Vandael et al, 2020).…”
Section: Discussionmentioning
confidence: 99%